Development of a Fast Simultaneous Analysis Method for Determination of Middle Rare-Earth Elements in Monazite Samples - Heru Agung Saputra; Anni Anggraeni; Abdul Mutalib; Husein Hernandi Bahti (Jurnal Kimia Sains dan Aplikasi, 2021)
Rare earth elements are a set of seventeen metallic elements, which is an essential part of many high-tech devices. Hence, analysis and/or separation of the rare earth elements from their mineral become crucial. A novel analysis method combining ultraviolet-visible spectroscopic and multivariate analysis was developed to determine middle rare earth elements quickly and simultaneously. The data collected from ultraviolet-visible spectroscopic were analyzed by multivariate analysis. The results showed that the developed method has good accuracy and precision with a detection limit of 1.375 (± 0.012), 0.332 (± 0.004), 42.117 (± 0.200), 1.767 (± 0.011), and 0.576 (± 0.002) ppm, respectively for samarium, europium, gadolinium, terbium, and dysprosium. The interference effect of ammonium iron(II) sulfate hexahydrate, manganese(III) sulfate hydrate, calcium carbonate, sodium carbonate, and lead(II) nitrate were examined. The reliability of the proposed method was evaluated using monazite samples. Conclusively, the developed method was successfully applied to determine the middle rare earth elements in monazite samples.